أثر التشريعات الرومانية على الحياة الاقتصادية والاجتماعية في بلاد المغرب - عطية سميرة (University of Eloued جامعة الوادي, 2023)
إن أثر التشريعات الرومانية الاقتصادي والاجتماعي في شمال إفريقيا منذ عام 146ق.م وحتى عام 429 م هو سرد لتطورات معقدة انكشفت خلال العصر الجمهورية والإمبراطوري، فخلال العصر الجمهوري، وقعت بلاد المغرب القديم تحت سيطرة روما بعد هزيمة قرطاج 146ق.م، مما مهد الطريق للتطورات القانونية اللاحقة، كما شهد العصر الجمهوري التوسع التدريجي للقوانين الرومانية وهياكل الحكم، ودمج شمال إفريقيا في الإطار القانوني الروماني الأوسع. كان لهذا التشريع تأثير عميق على اقتصاد شمال إفريقيا، حيث سهّل إنشاء الهياكل القانونية الرومانية في مجالات؛ الزراعة والري والضرائب والتجارة...، مما ساهم في النمو الاقتصادي والاستقرار، كما عزز بناء البنية التحتية، مثل الطرقات والموانئ، وربط المنطقة بالإمبراطورية الرومانية بشكل أوسع، بالإضافة الى ذلك ساعدت إصلاحات الأراضي وقوانين الملكية على تعزيز السيطرة الرومانية على الأراضي الزراعية الشاسعة، وتشكيل المشهد الاقتصادي لشمال إفريقيا. كما تركت التشريعات الاجتماعية بصماتها على مجتمع شمال إفريقيا، بحيث أثرت القوانين الرومانية على جوانب مختلفة من الحياة اليومية، من الهياكل الأسرية إلى الممارسات الاجتماعية الاخرى، الى جانب ان النظام القانوني الروماني أدخل إجراءات ومفاهيم قانونية جديدة أثرت في إقامة العدل في شمال إفريقيا، وتبعاً لذلك أدى انتشار بعض الحقوق والمواطنة الرومانية إلى الاندماج الاجتماعي الى حد كبير داخل المجتمعات المحلية. كانت إحدى النتائج الأكثر وضوحًا للتأثير الروماني ظهور مدن على الطراز الروماني في شمال إفريقيا، ازدهرت هذه المراكز الحضرية كمراكز للإدارة والتجارة والثقافة، حيث ظهرت المثُل الرومانية المعمارية والمدنية وفقاً لقوانين ودساتير الرومان، مما ساهم في تحضر المنطقة، ليس هذا فقط بل أصبح الفقهاء والمحامون الأفارقة منخرطين بعمق في القانون الروماني، وقاموا بتكييفه مع السياقات المحلية وساعدوا في تشكيل المشهد القانوني لشمال إفريقيا، كما أتاحت هذه الخبرة القانونية مزيجًا من التقاليد القانونية الرومانية والأصلية، مما يبرز الاندماج والاثر العميق بين التشريع الروماني والعادات المحلية، حيث كان أثر التشريعات الرومانية الاقتصادية والاجتماعية حتى عام 429م شاملاً ومتعدد الأوجه، أدى الى تطور النظم القانونية عبر العصور المختلفة، وإلى اندماج بلاد المغرب القديم في الإطار القانوني الروماني، كان لهذا التكامل تأثير تحويلي على اقتصاد ومجتمع المنطقة، بالإضافة الى التنمية الحضرية، مع تعزيز نمو الخبرة القانونية في البلاد. The impact of Roman economic and social legislation in the ancient Maghreb from 146 B.C to 429 A.D is a narrative of complex developments that unfolded during the Republican and Imperial eras. During the Republican era, ancient North African came under Roman control after the defeat of Carthage in 146 B.C, paving the way for subsequent legal developments, The Republican era also witnessed the gradual expansion of Roman laws and governance structures, integrating the ancient Maghreb into the broader Roman legal framework. This legislation had a profound effect on the economy of the ancient Maghreb, facilitating the establishment of Roman legal structures in areas such as agriculture, irrigation, taxation, and trade, contributing to economic growth and stability, as well as the enhancement of infrastructure like roads and ports, linking the region more extensively with the Roman Empire. Additionally, land reforms and property laws helped consolidate Roman control over vast agricultural lands and shaped the economic landscape of North Africa. The social legislation also left its mark on the ancient Maghreb society, as Roman laws influenced various aspects of daily life, from family structures to other social practices. The Roman legal system introduced new legal procedures and concepts that contributed to the establishment of justice in North Africa. As a result, the spread of certain Roman rights and citizenship led to significant social integration within local communities. One of the most evident outcomes of Roman influence was the emergence of Roman-style cities in North Africa, These urban centers thrived as hubs for administration, trade, and culture, showcasing Roman architectural and civic ideals based on Roman laws and constitutions, This not only cultivated urbanization in the region but also deeply engaged African jurists and lawyers in Roman law, adapting it to local contexts and contributing to the legal landscape of North Africa, This legal expertise allowed for a blend of Roman and indigenous legal traditions, highlighting the deep integration and influence between Roman legislation and local customs. The economic and social impact of Roman legislation until 429 A.D was comprehensive and multifaceted, driving the evolution of legal systems across different eras and integrating the ancient Maghreb within the Roman legal framework. This integration had transformative effects on the region's economy and society, along with urban development, while enhancing legal expertise within the region.
Keywords: التشريعات; التشريعات الرو; مانية; بلاد المغرب